Strategies for Managing Students' Reading Learning Difficulties in Madrasah Ibtidaiyah - Trinova, Zulvia; Zulfahmi, Zulfahmi; Jailani, M. Syahran; Saputra, Yogi (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2024)
This research is motivated by a problem in students' learning difficulties in reading, difficulty in combining letters into words, words into sentences and difficulty in pronouncing long sentences (halting). The strategies used by educators in learning to read by using direct and indirect learning strategies in the learning process, as well as using a reading guidance service strategy implemented after school in the library room which takes place 2-3 times a week. The purpose of this study is to: (1) describe the learning planning of educators in overcoming students 'learning difficulties in reading, (2) describe the strategies that educators undertake in overcoming students' reading difficulties, (3) describe the results of learning to read learners in class II B MIN I Pariaman City. The research method used is descriptive qualitative. Data collection techniques are observation, interview and documentation. Data triangulation is used to get the data, the data are analyzed by reducing irrelevant data, describing the data then drawing conclusions. The results of research on instructional learning planning in overcoming learning difficulties of students found that educators directly design RPP in Class II B. Making RPP is done at the beginning of the semester or before learning with the provisions of the contents of the RPP according to the needs of students in class II B. Strategies conducted by educators in overcoming the learning difficulties of reading class II B students use direct learning strategies (strategies that are centered on educators as the main source of learning) and indirect learning strategies (strategies that require students to be active in learning. The learning outcomes of students reading are 27 students, 22 including having good learning outcomes, it indicates that 84% of students get satisfying reading results and only 16% of other students are still under the KKM (Minimum Completeness Criteria).